Determining the ammonia capture efficiency in combined contact device - Філенко, Олеся Миколаївна; Гринь, Світлана Олександрівна (Technology audit and production reserves, 2014)
The studies of ammonia absorption in the combined contact device are given in the paper. The main goal of the research is to determine the optimal operating conditions for the combined contact device (CCD), consisting of a perforated plate and regular packing. The effect of the gas velocity, spraying density, area of free section of grates and diameter of grates on the ammonia absorption rate is considered. These studies allow to determine operating modes and design parameters of CCD. As a result, it is found that the decrease in the free section area reduces the contact step effectiveness, spraying density in the CCD has effect only to 8–10 m3/m2h. When using the packing N1, COP significantly increases depending on the ammonia concentration. Thus, we can state that ammonia absorption efficiency in the CCD, operating in the mode of highly-turbulized foam confirms that the CCD design leads to intense flow mixing, retards the growth of the gas content and promotes the growth of the contact surface of phases and their renewal rate. This eliminates the raw gas leakage from the absorption compartment in the atmosphere.